Development of Contract Management SOP with it Service Providers Supplier Based on the Framework Cobit 5 and ITIL V3 Hospital Case Study Dr Ramelan Navy - Puspadini, Yundha (Jurnal Manajemen Informatika Medicom (JMI), 2024)
RSAL Dr. Ramelan is a naval hospital in Surabaya. It is currently developing its Management Information Systems (MIS) with the supplier of IT (Information Technology) service providers. Problems arose when the management change interfere with MIS development. The current management wanted to change MIS supplier before the development process is completed. This can cause financial and time losses. The process of supplier selection, negotiation, contracting and fulfillment control of supplier contracts to always fit the needs of the business is conducted at the Supplier Management. This study aims to make a reference to the management of IT service provider suppliers contracts in the form of SOP (Standard Operating Procedure) which is based on the COBIT 5 framework domain APO10 Manage Supplier and ITIL V3 Supplier Management. Formulation of IT service providers supplier contract management in RSAL Dr. Ramelan SOP document is carried out in four stages. The first stage is the observation of IT services in RSAL Dr. Ramelan. The second stage is the stage of the analysis. This stage is to identify COBIT 5 Manage Supplier and ITIL V3 Supplier Management activities and mapping the activities. Having formed a new activity, adjustments are made to the Regulation of the President of the Republic of Indonesia No. 54 of 2010 concerning the Procurement of Goods and Services. In the third stage, SOP document preparation is done by decomposition of these activities to become sequential action steps. The last stage is the stage of evaluation and improvement, which begins with the verification done in RSAL Dr. Ramelan, then the improvement is done based on the results of verification. The result of this study is an IT service providers supplier contract management SOP document that has been tailored to the condition in RSAL Dr. Ramelan. From the result of the evaluation, it is known that the SOP produced was still in need for improvement in terms of grammar, role and order activity. The SOP document that has been evaluated before has been corrected and improved based on the feedback given by RSAL Dr. Ramelan.